Determinants of successful virtual teams with special reference to the information technology sector in Sri Lanka (Vallis Aurea, 2024)
Purpose: Technological advancements, globalization, and crisis situations have compelled society to adopt a virtual platform. In light of this scenario, the purpose of this study was to ascertain the determinants that influence the success of virtual teams in the Sri Lankan context in order to enhance the benefits of the virtual platform. Design and approach: Research study was based on quantitative approach and focused on the actual data that received from the respondents. Methodology: This was a cross-sectional study involving employees in the Information Technology (IT) sector. The data collection technique used was a structured questionnaire combined with a simple random sampling technique. Correlation and simple linear regression analysis were used to analyze the data. Findings: The research reveals that trust, leadership, and communication all have a significant positive impact on successful virtual teamwork independently, while also ensuring a positive relationship between the variables. Originality of the research: The uniqueness of this study is demonstrating how those factors contribute to the conversion of traditional teams to modern teams, thereby increasing the likelihood of the final outcome in a fruitful manner.